Personnel Administration Management Strategy of the Fire and Rescue Department of Yogyakarta City - Nurjanah, Nurjanah; Sulistyowati, Eny (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2026)
This study examines the personnel administration management strategies within the Fire and Rescue Department of Yogyakarta City. The research focuses on identifying the practices, challenges, and improvements in managing human resources, particularly within a public service organization such as the fire and rescue department. By using a qualitative approach, this study analyzes the organizational structure, recruitment processes, training programs, and employee performance evaluation systems implemented by the department. Additionally, it explores the integration of technology and communication systems in enhancing administrative efficiency. The findings reveal that while there are notable efforts to optimize human resource management, challenges such as limited budget allocations, the need for more advanced training programs, and the adoption of more modern management tools still persist. Recommendations are provided to improve administrative practices through better resource allocation, enhanced staff training, and the implementation of digital tools to streamline operations. This study offers valuable insights for improving public sector management, specifically in critical service organizations like fire and rescue departments.